Retrievals of High‐Latitude Surface Emissivity Across the Infrared From High‐Altitude Aircraft Flights. Issue 22 (21st November 2020) - Murray, Jonathan E.; Brindley, Helen E.; Fox, Stuart; Bellisario, Christophe; Pickering, Juliet C.; Fox, Cathryn; Harlow, Chawn; Smith, Maureen; Anderson, Doug; Huang, Xianglei; Chen, Xiuhong; Last, Alan; et al.
Abstract: We present retrievals of infrared spectral surface emissivities spanning the far infrared and mid‐infrared from aircraft observations over Greenland, taken at an altitude of 9.2 km above sea level. We describe the flight campaign, available measurements, and the retrieval method. The principal barriers to reducing uncertainty in the emissivity retrievals are found to be instrumental noise and our ability to simultaneously retrieve the underlying surface temperature. However, our results indicate that using the instrumentation available to us it is possible to retrieve emissivities from altitude with an uncertainty of 0.02 or better across much of the infrared. They confirm that the far‐infrared emissivity of snow and ice surfaces can depart substantially from unity, reaching values as low as 0.9 between 400 and 450 cm −1 . They also show good consistency with retrievals from the same flight made from near‐surface observations giving confidence in the methodology used and the results obtained for this more challenging viewing configuration. To the best of our knowledge, this is the first time that far‐infrared surface emissivity has been retrieved from altitude and demonstrates that the methodology has the potential to be extended to planned satellite far‐infrared missions. Key Points: Retrievals of surface emissivity and temperature across the thermal infrared from high‐altitude aircraft measurements are reported Retrieved far‐infrared emissivities are significantly less than unity, showing consistency with near‐surface retrievals in the same flight This emissivity and surface temperature retrieval methodology is applicable to proposed satellite instruments covering the thermal infrared